A review on the applications of signal processing techniques for mitigating dementia-related hearing implications through a wide-band equalizer - Copiaco, Abigail; ElKouly, Abeer; Abdulaziz, Nidhal; Alkhatib, Obada; Khelalfa, Halim; Fareq Malek, Mohamed; Lasrado, Flevy (International Journal of Engineering and Technology, 2019)
Dementia is a progressive cognitive ailment that affects its patientsâ€™ daily regime and independence. Over the years, the number of people experiencing dementia is continuously rising, signifying the apparent need for progress within the field. Studies have explored the possible connection between hearing impairment and dementia. In order to minimize the effects of this hearing impairment, existing works have focused on invasive processes in order to bring the hearing curve, referred to as audiogram, back to the normal curve of hearing. However, considering the fact that dementia involves aged individuals, invasive processes are deemed risky for their overall health and well-being, besides their high costs and complexity. Therefore, in this paper, we explore and compare non-invasive processes, which are based on signal processing techniques, in order to design a hearing equalization filter that is translatable to a wearable and mobile device, in order to eliminate the risks of invasive chip embedding.Â